百度试题 结果1 题目Solve the equation cos 2x° =-0.7, for x in the interval 0≤ x≤ 360. 相关知识点: 试题来源: 解析 67.2,112.8,247.2,292.8 反馈 收藏
Dividing the equation by cos2x, we can express the differential equation in the following form: {eq}\displaystyle y'+\frac{1}{\cos^2...Become a member and unlock all Study Answers Try it risk-free for 30 days Try it risk-free Ask a question Our experts...
Find the general solution of the following equation: y" + 2y' + 2y = 3 sin 2x Find the particular solution y(p) for the given equation. y'' + y = \sin x + x \cos x Find a particular solution y_p of the given equation. y'' - 2 y' + 2 y = e^x sin x...
Show that | sin x - cos x | \leq \sqrt2 for all x. Solve the equation. 2 sin^2x - cos x-1 = 0 Prove the identity algebraically: cos x / 1 + sin x = sec x - tan x Prove that the equation 3x + 2 \sin x - 2 = 0 has exactly one real root using the interm...
www.nature.com/scientificreports OPEN Evolution equation for quantum coherence received: 26 April 2016 accepted: 13 June 2016 Published: 07 July 2016 Ming-Liang Hu1 & Heng Fan2,3 The estimation of the decoherence process of an open quantum system is of both theoretical significance and ...
However, the matrix equation formulation we propose in this paper still holds for more general domains and operators . We discretize the problem (1.2) in both space and time, and, for the sake of simplicity, we assume that a finite difference method is employed in the space discretization ...
Step 4: Use the identity for cos2xRecall that cos2x=1−2sin2x. Thus, we can express 1−4sin2x as: 1−4sin2x=1−2(2sin2x)=1−2sin2x−2sin2x=cos2x−2sin2x So we can rewrite our equation as: cosx⋅(1−4sin2x)=sinx Step 5: Set the equation in terms of tanx...
sin(x)+cos(y)=0.5 2x−3y=1 cos(x^2)=y (x−3)(x+3)=y^2 y=x^2If you don't include an equals sign, it will assume you mean "=0"It has not been well tested, so have fun with it, but don't trust it.If it gives you problems, let me know.Note...
百度试题 结果1 题目 The graph of the equation y = 2 cos 2x, 0 ≤ x ≤ 2π, has a line of symmetry atA: x = π B: y = 2 C: the x‑axisD: x = π/(4) 相关知识点: 试题来源: 解析 ANone 反馈 收藏
Calculate an invariant for the pendulum motion by forming the ratio dϕdtdθdt=−g Sin[θ]Lϕcanceling dt, separating variables, and integrating. Prove that E[ϕ[t],α[t]] = L2 ϕ2[t]+g(1 − Cos[θ[t]]) is constant on solutions of the pendulum equations. Make a con...